STUDI PENERJEMAHAN METAFORA DALAM NASKAH DRAMA DI UNIVERSITAS NASIONAL JAKARTA - Imelda Malawaty Simorangkir; Dewi Mutiara Indah Ayu (Universitas Nasional, 2017)
The purpose of the research study in metaphore in the English text literary at National University is to enlarge the knowlodge in the translation of metaphore and the types of metaphore categorize that have been found in English text literary especially in role plays. Since the research is begun, translating the metaphore text was not the easiest once. In fact, metaphore becomes the part of figurative language which is refers to two parts like Implicit and Expicit. Literary text has been used by the English students as their data because they found metaphore sentences to be analyze in their research. This research uses descriptive qualitative research that focus on observation during the class. Therefore, all the data were collected dan arranged in dictionary that would be useful for the students in faculty of letters.